Mentesh Tepe, an early settlement of the Shomu-Shulaveri Culture in Azerbaijan. (22nd February 2016) - Lyonnet, Bertille; Guliyev, Farhad; Bouquet, Laurence; Bruley-Chabot, Gaëlle; Samzun, Anaïck; Pecqueur, Laure; Jovenet, Elsa; Baudouin, Emmanuel; Fontugne, Michel; Raymond, Pascal; Degorre, Emeline; Astruc, Laurence; et al.
Abstract: Excavations at Mentesh Tepe, western Azerbaijan, have unearthed Neolithic levels dated to an early stage of the Shomu-Shulaveri Culture, with a specific material culture and several inhumations among which a multiple burial. At that stage, already a full domestication of plants and animals is evident. Many questions have been raised concerning the origins of this culture, and its end is also still obscure. Relations with societies in the north-Mesopotamian area have again recently been evidenced at its beginnings. Mentesh Tepe, with its exceptional succession of occupations from the Neolithic to the Early Bronze Age, could help providing some clues for the links between the Neolithic and the Chalcolithic periods. The site is presented here under different points of views (architecture, burials, material culture) but in a preliminary stage since many studies are still in progress. Questions are raised about the climate and the apparent absence of pre- and post-Shomu-Shulaveri Culture possibly due to silting or erosion processes linked with the mobility of the Caspian Sea level.